Metal lithium / mixed conductive interlayer / inorganic solid electrolyte integrated electrode, preparation method thereof and battery

By introducing a heteroatom-doped hard carbon skeleton intermediate layer at the interface of solid metal lithium batteries, the problem of incompatibility between metal lithium and inorganic solid electrolyte interface is solved, and the interface is low impedance, high stability and safety is achieved.

CN119905520AActive Publication Date: 2025-04-29CENT SOUTH UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411993616.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-29
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

In solid metal lithium batteries, there are incompatibility problems with the interface between metal lithium and inorganic solid electrolytes, resulting in high impedance of the interface, growth of lithium dendrites and safety hazards, limiting the commercial application of lithium metal negative electrodes.

Method used

A hard carbon skeleton with heteroatom doped is used as a hybrid conductive intermediate layer. By forming a doped hard carbon layer on the surface of the inorganic solid electrolyte sheet and lithiating the interface between the metal lithium and the solid electrolyte, an intermediate layer with ionic/electron hybrid conductive properties is formed to improve interface performance.

Benefits of technology

It significantly reduces the impedance of the metal lithium/inorganic solid electrolyte interface, reduces the interface stress, inhibits the growth of lithium dendrites, and improves the cycle stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905520A_ABST
    Figure CN119905520A_ABST
Patent Text Reader

Abstract

The invention provides a metal lithium / mixed conductive interlayer / inorganic solid electrolyte integrated electrode and a preparation method and application thereof. The integrated electrode comprises an inorganic solid electrolyte sheet, a mixed conductive intermediate layer and a metal lithium layer, the mixed conductive intermediate layer is located on one surface of the inorganic solid electrolyte sheet, and the metal lithium layer is located on the surface of the mixed conductive intermediate layer; the mixed conductive intermediate layer is a heteroatom-doped hard carbon skeleton lithiation product; the hard carbon skeleton lithiation product comprises hard carbon, LiCx, and one or more of LiF, Li2S, Li3N and LiCl. The integrated electrode provided by the invention can effectively improve the wettability of a metal lithium and inorganic solid electrolyte interface and obviously reduce the interface impedance, and the formed mixed conductive intermediate layer can adapt to the volume change generated in the cycle process, reduce the interface stress, homogenize the interface electric field, induce the uniform nucleation and deposition of the metal lithium and inhibit the growth of lithium dendrites. The provided integrated electrode can be widely applied to solid-state batteries, quasi-solid-state batteries, semi-solid-state batteries and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state metal lithium batteries, and specifically relates to a metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode and a preparation method and application thereof. Background Art

[0002] Solid-state metal lithium batteries have the advantages of high safety, high energy density, high power density, and long cycle life, and are considered to be a strong competitor for the next generation of energy storage technology. The key component of solid-state metal lithium batteries is solid electrolytes. Compared with traditional liquid batteries, solid electrolytes that are not easy to leak or explode completely replace liquid electrolytes and diaphragms, greatly reducing the risk of thermal runaway of batteries. Secondly, due to the high mechanical strength of solid electrolytes, they can effectively inhibit the formation and growth of lithium dendrites. At the same time, the combination of solid electrolytes and diaphragms also reduces the mass and volume of the battery pack, making the battery lighter and more efficient.

[0003] However, solid-state metal lithium batteries still face some challenges on the road to commercialization, and the most urgent issue to be solved is the metal lithium / solid electrolyte interface problem. Due to its extremely high reducibility, metal lithium is easily exposed to high-valent metal cations (such as Ti) in the electrolyte when it comes into contact with the solid electrolyte in a solid-state battery. 4+ ,Ge 4+ At the same time, due to the rigidity of the solid electrolyte itself and the problem of residual alkali on the surface, the metal lithium and the solid electrolyte can only achieve "point-to-point" contact at the interface, which not only hinders the transmission of lithium ions, but also increases the internal resistance of the battery, resulting in a decrease in battery performance. In some extreme cases, it may even cause lithium dendrites to penetrate the solid electrolyte, causing safety problems. The unstable metal lithium / solid electrolyte interface and the serious problem of lithium dendrite growth have severely limited the commercial application of lithium metal anodes. Proposing an interface modification strategy to solve the incompatibility problem of metal lithium / solid electrolyte interface and effectively inhibit the generation of lithium dendrites is the key to solving the above problems.

[0004] In recent years, many researchers have introduced metal intermediate layers at the metal lithium / solid electrolyte interface by magnetron sputtering, atomic layer deposition, etc. to improve the interface performance, but this intermediate layer plays a modifying role through limited chemical reactions or alloying with metal lithium. Due to poor ductility and compressibility, the interfacial reaction products cannot withstand huge volume changes and will produce cracks at the metal lithium / solid electrolyte interface. Based on this, researchers hope to reduce the interfacial stress during volume expansion by introducing a soft interface. CN110444731A uses a composite method of ionic liquid and polymer to promote the film formation of ionic liquid at the metal lithium / solid electrolyte interface, thereby introducing a flexible modification layer for modification, reducing the stress change of the solid battery during the cycle; CN117638074A prevents the side reaction between metal lithium and the inorganic solid electrolyte by curing the protective layer formed by polymer hydrogel and lithium salt, so that the battery has better cycle performance. However, these soft interfaces lack a certain mechanical strength and cannot effectively inhibit the growth of lithium dendrites at high current density, thus causing battery short circuit, and the introduced polymers tend to reduce the ionic conductivity at the interface; CN118472253A uses a compound of graphene and boron to form a self-supporting artificial intermediate layer with good ductility and not too soft to regulate the metal lithium / sulfide solid electrolyte interface. Although the interfacial ion / electronic conductivity is improved, relevant studies have shown that the long-range ordered layered structure inside the graphene is not conducive to the vertical transport of lithium ions at the interface. Summary of the invention

[0005] In response to the above technical problems, the present application provides a metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode and a preparation method and application thereof.

[0006] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, a metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode is provided, comprising an inorganic solid electrolyte sheet, a mixed conductive intermediate layer and a metal lithium layer, wherein the mixed conductive intermediate layer is located on one surface of the inorganic solid electrolyte sheet, and the metal lithium layer is located on a surface of the mixed conductive intermediate layer away from the inorganic solid electrolyte sheet; the mixed conductive intermediate layer is a lithiated product of a hard carbon skeleton doped with heteroatoms; the heteroatoms doped with the hard carbon skeleton are one or more of N, F, S, Cl, Na, and K; the lithiated product of the hard carbon skeleton doped with heteroatoms comprises hard carbon and LiC x , and one or more substances among LiF, Li2S, Li3N, and LiCl.

[0007] Furthermore, the inorganic solid electrolyte sheet is one or more of an oxide solid electrolyte, a halide solid electrolyte, and a sulfide solid electrolyte.

[0008] Furthermore, the inorganic solid electrolyte sheet is selected from one or more of garnet-type oxide solid electrolytes, sodium superion conductor solid electrolytes, lithium superion conductor solid electrolytes, and perovskite solid electrolytes.

[0009] Furthermore, the garnet-type oxide solid electrolyte is one or more of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum zirconium niobium oxide (LLZNO), and lithium gallium lanthanum zirconium oxide (LGLZO).

[0010] Furthermore, the sodium superion conductor type solid electrolyte is one or more of lithium aluminum titanium phosphate (LATP) and lithium aluminum germanium phosphate (LAGP).

[0011] Furthermore, the lithium superion conductor type solid electrolyte is one or more of lithium germanium vanadium oxide (LGVO) and lithium germanium phosphorus sulfur (LGPS).

[0012] Furthermore, the perovskite solid electrolyte is ABO3, wherein A is one or more of Ca, Sr, and La; and B is one or more of Al and Ti.

[0013] Furthermore, the thickness of the doped hard carbon layer is 2-3 μm.

[0014] In a second aspect, a method for preparing a metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode is provided, comprising: Forming a doped hard carbon layer on one surface of the inorganic solid electrolyte sheet to obtain an inorganic solid electrolyte sheet having a doped hard carbon layer on the surface; the doping atoms of the doped hard carbon layer are one or more of N, F, S, K, Na, and Cl; Under vacuum conditions with a water content of less than 0.01ppm or in an inert gas atmosphere, the metal lithium sheet is first heated to a molten state, and then the side of the inorganic solid electrolyte sheet having the doped hard carbon layer is placed on the molten metal lithium, and the lithiation reaction is carried out by keeping the temperature at a certain temperature to obtain a metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode.

[0015] Furthermore, the thickness of the mixed conductive intermediate layer is 2-3 μm.

[0016] Furthermore, the forming of a doped hard carbon layer on the surface of the inorganic solid electrolyte sheet comprises: coating a carbon source precursor on the surface of the inorganic solid electrolyte sheet, and then pyrolyzing the carbon source precursor in an argon atmosphere or a nitrogen atmosphere.

[0017] Furthermore, the carbon source precursor includes biomass, and optionally sugars and synthetic resins.

[0018] Furthermore, the sugar is selected from at least one of starch, glucose and sucrose; Furthermore, the synthetic resin is selected from at least one of phenolic resin, epoxy resin and urea-formaldehyde resin; Furthermore, the biomass is selected from at least one of egg white, honey, coconut shell, walnut shell, straw, wood, tea shell, and bamboo powder; Further, the pyrolysis includes: firstly performing a low temperature heat treatment at 400-500°C, and then performing a high temperature heat treatment at 600-1000°C; Furthermore, the time of the low-temperature heat treatment is 2 to 4 hours; the time of the high-temperature heat treatment is 2 to 4 hours.

[0019] Furthermore, the temperature of the heated lithium metal sheet is 200-350°C.

[0020] Furthermore, the insulation temperature is 300-400°C.

[0021] Furthermore, the inorganic solid electrolyte sheet is one or more of an oxide solid electrolyte, a halide solid electrolyte, and a sulfide solid electrolyte.

[0022] Furthermore, the inorganic solid electrolyte sheet is selected from one or more of garnet-type oxide solid electrolytes, sodium superion conductor solid electrolytes, lithium superion conductor solid electrolytes, and perovskite solid electrolytes.

[0023] Furthermore, the garnet-type oxide solid electrolyte is one or more of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum zirconium niobium oxide (LLZNO), and lithium gallium lanthanum zirconium oxide (LGLZO).

[0024] Furthermore, the sodium superion conductor type solid electrolyte is one or more of lithium aluminum titanium phosphate (LATP) and lithium aluminum germanium phosphate (LAGP).

[0025] Furthermore, the lithium superion conductor type solid electrolyte is one or more of lithium germanium vanadium oxide (LGVO) and lithium germanium phosphorus sulfur (LGPS).

[0026] Furthermore, the perovskite solid electrolyte is ABO3, wherein A is one or more of Ca, Sr, and La; and B is one or more of Al and Ti.

[0027] Furthermore, the mixed conductive intermediate layer is a lithiated product of a hard carbon skeleton doped with a heteroatom; the lithiated product of the hard carbon skeleton doped with a heteroatom includes LiC x , LiF, Li2S, Li3N, LiCl and hard carbon.

[0028] In a third aspect, a battery is provided, comprising the aforementioned metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode or the metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode prepared by the aforementioned preparation method, wherein the battery is a semi-solid-state battery, a quasi-solid-state battery or an all-solid-state battery.

[0029] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: In order to solve the wettability problem of metal lithium / inorganic solid electrolyte interface, it is proposed to improve the wettability of solid electrolyte to metal lithium by using the mixed conductive intermediate layer produced by the lithiation of heteroatom-doped hard carbon skeleton. The lithiated hard carbon has excellent lithium affinity and significantly reduces the interface impedance.

[0030] In order to solve the stress problem caused by volume expansion at the interface of metal lithium / inorganic solid electrolyte, it is proposed to reduce the interface stress by using the mixed conductive intermediate layer produced by the lithiation of the hard carbon skeleton doped with heteroatoms. The hard carbon skeleton after lithiation has the good ductility and compressibility of carbon itself, which can adapt to the volume change during the cycle of solid metal lithium battery and reduce the interface stress.

[0031] In order to solve the problem of lithium dendrite growth at the interface of metal lithium / inorganic solid electrolyte, a hybrid conductive interlayer produced by the lithiation of a heteroatom-doped hard carbon skeleton is proposed to achieve a dendrite-free interface. The hybrid conductive interlayer can homogenize the interfacial electric field and provide a fast and smooth transmission path for ions, thereby inducing uniform nucleation and deposition of metal lithium at the interface and inhibiting the growth of lithium dendrites.

[0032] The integrated electrode provided can be widely used in solid-state batteries, quasi-solid-state batteries, semi-solid-state batteries, etc.

[0033] The preparation method of the provided metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode is simple and easy to implement, and is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 XRD patterns of the heteroatom-doped hard carbon skeletons provided in Example 1 and Example 3.

[0036] Figure 2This is a scanning electron microscope cross-sectional image of the modified oxide solid electrolyte ceramic sheet provided in Example 1.

[0037] Figure 3 This is the deposition morphology of the modified metallic lithium on the heteroatom-doped hard carbon skeleton in Example 1.

[0038] Figure 4 This is the AC impedance diagram of the symmetrical battery after the modification method provided in Example 1.

[0039] Figure 5 The symmetrical battery after the modification method provided in Example 1 is at 1.0 mA / cm 2 Long-term cycling performance at different current densities.

[0040] Figure 6 This is a diagram of the critical current density of the symmetrical battery after modification of Example 1 and Comparative Example 1.

[0041] Figure 7 This is a scanning electron microscope cross-sectional image of the interface of a symmetrical battery after the modification method provided in Example 1 and after long-term cycling.

[0042] Figure 8 This is the XPS graph of the mixed conductive intermediate layer in Example 1.

[0043] Fig. 9 This is a charge and discharge curve diagram of the semi-solid metal lithium battery constructed in Example 1 at 0.1C.

[0044] Fig.10 This is a charge and discharge curve diagram of the quasi-solid-state metal lithium battery constructed in Example 2 at 0.1C.

[0045] Fig.11 The symmetrical battery after the modification method provided in Comparative Example 1 is at 0.1 mA / cm 2 Long-term cycling performance at different current densities.

[0046] Fig.12 Schematic diagram of the modification method of Example 1 and Comparative Example 1.

[0047] Fig.13 The symmetrical battery after the modification method provided in Comparative Example 2 is at 0.1 mA / cm 2 Long-term cycling performance at different current densities. DETAILED DESCRIPTION

[0048] Some embodiments of the present invention provide a metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode, comprising an inorganic solid electrolyte sheet, a mixed conductive intermediate layer and a metal lithium layer, wherein the mixed conductive intermediate layer is located on one surface of the inorganic solid electrolyte sheet (i.e., the mixed conductive intermediate layer covers or coats one surface of the inorganic solid electrolyte sheet), and the metal lithium layer is located on the surface of the mixed conductive intermediate layer away from the inorganic solid electrolyte sheet (i.e., the metal lithium layer covers or coats the surface of the mixed conductive intermediate layer away from the inorganic solid electrolyte sheet); the mixed conductive intermediate layer is a lithiated product of a hard carbon skeleton doped with heteroatoms; the heteroatoms doped with the hard carbon skeleton are one or more of N, F, S, Cl, Na, and K; the lithiated product of the hard carbon skeleton doped with heteroatoms comprises hard carbon and LiC x , and one or more substances among LiF, Li2S, Li3N, and LiCl.

[0049] In some preferred embodiments, the inorganic solid electrolyte sheet is one or more of an oxide solid electrolyte, a halide solid electrolyte, and a sulfide solid electrolyte; further preferably, the inorganic solid electrolyte sheet is selected from one or more of a garnet-type oxide solid electrolyte, a sodium superion conductor solid electrolyte, a lithium superion conductor solid electrolyte, and a perovskite solid electrolyte; further preferably, it is a garnet-type oxide solid electrolyte.

[0050] The garnet-type oxide solid electrolyte is one or more of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum zirconium niobium oxide (LLZNO), and lithium gallium lanthanum zirconium oxide (LGLZO).

[0051] The sodium superion conductor type solid electrolyte is one or more of lithium aluminum titanium phosphate (LATP) and lithium aluminum germanium phosphate (LAGP).

[0052] The lithium superion conductor type solid electrolyte is one or more of LGVO and LGPCO.

[0053] The perovskite solid electrolyte is ABO3, wherein A is one or more of Ca, Sr, and La; and B is one or more of Al and Ti.

[0054] In some preferred embodiments, the thickness of the mixed conductive intermediate layer is 2-3 μm, for example, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3 μm, etc.

[0055] Based on the ion / electron mixed conductive intermediate layer, an interface modification method was designed, which can not only reduce the interface stress, improve the wettability of the metal lithium / inorganic solid electrolyte interface, but also effectively inhibit the growth of lithium dendrites. Specifically, some embodiments of the present invention provide a method for preparing a metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode, comprising: Forming a doped hard carbon layer on one surface of the inorganic solid electrolyte sheet to obtain an inorganic solid electrolyte sheet having a doped hard carbon layer on the surface; the doping atoms of the doped hard carbon layer are one or more of N, F, S, K, Na, and Cl; Under vacuum conditions with a water content of less than 0.01ppm or in an inert gas atmosphere, the metal lithium sheet is first heated to a molten state, and then the side of the inorganic solid electrolyte sheet having the doped hard carbon layer is placed in the molten metal lithium, and the sheet is kept warm at a certain temperature for a lithiation reaction, so that the hard carbon skeleton on its surface undergoes a lithiation reaction with the metal lithium to obtain an intermediate layer with mixed conductive properties, and then a mixed conductive intermediate layer containing a lithiated product of the hard carbon skeleton doped with heteroatoms is formed at the interface between the negative electrode and the solid electrolyte, so as to modify the interface between the negative electrode and the solid electrolyte and obtain a metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode.

[0056] A carbon source precursor is used to perform high-temperature pyrolysis on the surface of an inorganic solid electrolyte to introduce a layer of hard carbon skeleton doped with heteroatoms. Compared with graphite and soft carbon, the hard carbon skeleton after lithiation has good ductility and flexibility of carbon itself, and also has a certain mechanical strength, which can significantly improve the wettability of the interface, reduce the interfacial stress and effectively inhibit the growth of lithium dendrites. The metal lithium negative electrode melted at high temperature is placed on this hard carbon skeleton and undergoes a lithiation reaction with it, thereby forming an intermediate layer with ion / electron mixed conductive properties at the interface between the negative electrode and the inorganic solid electrolyte, and the molten metal lithium adheres to the intermediate layer to prepare a metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode. This method can significantly improve the interface wettability and stability of the inorganic solid electrolyte and the metal lithium negative electrode. The introduced mixed conductive intermediate layer can homogenize the interface electric field, provide a fast and smooth ion transmission path, thereby promoting the uniform nucleation and deposition of metal lithium at the interface, realizing a dendrite-free interface, and improving the cycle stability and safety of solid-state batteries at high current density in a simple and low-cost way.

[0057] In some preferred embodiments, the thickness of the doped hard carbon layer is 2-3 μm, for example, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3 μm, etc.

[0058] In some preferred embodiments, the step of forming a doped hard carbon layer on the surface of the inorganic solid electrolyte sheet comprises: coating a carbon source precursor on the surface of the inorganic solid electrolyte sheet and then pyrolyzing the carbon source precursor in an argon atmosphere or a nitrogen atmosphere.

[0059] One or more carbon source precursors are uniformly mixed and dispersed by one or more methods such as stirring, grinding, ball milling, etc., and then coated on the surface of the inorganic solid electrolyte sheet.

[0060] The coating is selected from one or more methods such as spin coating, coagulation, spraying, etc.

[0061] The inert gas may be any conventional inert gas in the art, such as argon, helium, neon, argon, etc.

[0062] In some preferred embodiments, heating the molten lithium metal sheet and heat-insulating the lithiation reaction are both carried out in a glove box.

[0063] In some preferred embodiments, the carbon source precursor includes biomass, and optionally sugars and synthetic resins, that is, the carbon source precursor can be biomass, or a mixture of biomass and at least one of sugars and synthetic resins.

[0064] In some preferred embodiments, the sugar is selected from at least one of starch, glucose and sucrose.

[0065] In some preferred embodiments, the synthetic resin is selected from at least one of phenolic resin, epoxy resin and urea-formaldehyde resin.

[0066] In some preferred embodiments, the biomass is selected from at least one of egg white, honey, coconut shell, walnut shell, straw, wood, tea oil shell, and bamboo powder.

[0067] In some preferred embodiments, the pyrolysis includes: first performing a low-temperature heat treatment at 400-500°C (for example, 400°C, 420°C, 450°C, 480°C, 500°C, etc.), and then performing a high-temperature heat treatment at 600-1000°C (for example, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, etc.).

[0068] In some preferred embodiments, the temperature of heating the lithium metal sheet is 200-350°C, for example, 200°C, 220°C, 250°C, 280°C, 300°C, 320°C, 350°C, etc.

[0069] In some preferred embodiments, the insulation temperature is 300-400°C, for example, 300°C, 320°C, 350°C, 380°C, 400°C, etc.

[0070] In some preferred embodiments, the inorganic solid electrolyte sheet is one or more of an oxide solid electrolyte, a halide solid electrolyte, and a sulfide solid electrolyte; preferably, the inorganic solid electrolyte sheet is selected from one or more of a garnet-type oxide solid electrolyte, a sodium superion conductor solid electrolyte, a lithium superion conductor solid electrolyte, and a perovskite solid electrolyte; further preferably, it is a garnet-type oxide solid electrolyte.

[0071] The garnet-type oxide solid electrolyte is one or more of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum zirconium niobium oxide (LLZNO), and lithium gallium lanthanum zirconium oxide (LGLZO).

[0072] The sodium superion conductor type solid electrolyte is one or more of lithium aluminum titanium phosphate (LATP) and lithium aluminum germanium phosphate (LAGP).

[0073] The lithium superion conductor type solid electrolyte is one or more of lithium germanium vanadium oxide (LGVO) and lithium germanium phosphorus sulfur (LGPS).

[0074] The perovskite solid electrolyte is ABO3, wherein A is one or more of Ca, Sr, and La; and B is one or more of Al and Ti.

[0075] In some preferred embodiments, the mixed conductive intermediate layer is a lithiated product of a hard carbon skeleton doped with a heteroatom; the lithiated product of a hard carbon skeleton doped with a heteroatom includes LiC x , LiF, Li2S, Li3N, LiCl and hard carbon.

[0076] The present invention also provides a battery, comprising the aforementioned metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode or the metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode prepared by the aforementioned preparation method, wherein the battery is a semi-solid battery, a quasi-solid battery or an all-solid-state battery.

[0077] In some embodiments, the positive electrode active material in the positive electrode of the solid-state battery is selected from one or more of layered positive electrode materials [lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA), lithium manganese-rich based positive electrode materials], spinel positive electrode materials [lithium manganese oxide (LiMn2O4)], and olivine positive electrode materials [lithium iron phosphate (LiFePO4)].

[0078] In some embodiments, the solid-state battery further includes the positive electrode side electrolyte; the positive electrode side electrolyte is one or both of a liquid electrolyte and a polymer solid electrolyte.

[0079] Some embodiments also provide a method for preparing the above-mentioned battery, comprising the following steps: The aforementioned metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode, optional electrolyte or polymer electrolyte and positive electrode plate are assembled into a battery. It is worth noting that when the assembled battery is a semi-solid battery, an electrolyte can be added, and when the assembled battery is a quasi-solid battery, a polymer electrolyte can be added.

[0080] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.

[0081] Example 1 A method for optimizing the negative electrode interface of a solid-state metal lithium battery based on a mixed conductive intermediate layer, wherein the solid electrolyte is a garnet-type oxide solid electrolyte LLZTO (lithium lanthanum zirconium tantalum oxide) ceramic sheet, the carbon source precursor is a biomass precursor egg white and a sugar precursor sucrose; the positive electrode side electrolyte is a liquid electrolyte; and the positive electrode material is NCM811. (1) Preparation of precursor: First, thoroughly mix egg white and sucrose in a beaker and beat with a stirrer to form a meringue in which the protein and sucrose molecules are cross-linked.

[0082] (2) Interface modification: The oxide solid electrolyte LLZTO ceramic sheet was placed on a heating table for low-temperature preheating, and then the protein cream was coated on the surface of the preheated ceramic sheet. The ceramic sheet coated with protein cream was sent to a tubular furnace and heated to 400°C at 5°C / min for pretreatment, kept warm for 2 hours, and then heated to 800°C at 5°C / min for high-temperature pyrolysis and kept warm for 2 hours, thereby introducing a hard carbon skeleton (doped atoms are N, F, S, K, Na, Cl) with a thickness of 2~3μm on the surface of the ceramic sheet, and an oxide solid electrolyte ceramic sheet LLZTO@C with a hard carbon skeleton introduced on the surface was obtained. The XRD pattern is shown in the figure. Figure 1 As shown in the SEM images Figure 2 As shown, from Figure 2 It can be seen that the thickness of the hard carbon layer is relatively uniform and is in very close contact with LLZTO, which is beneficial to reducing the interface impedance.

[0083] (3) Assembling the negative electrode metal lithium: Place the metal lithium sheet on a heating table and heat it to a molten state at 300°C, place the modified oxide solid electrolyte ceramic sheet LLZTO@C into the molten metal lithium, and keep it at 350°C for a period of time to initiate the lithiation reaction, thereby forming a mixed conductive intermediate layer containing the lithiated product of the hard carbon skeleton doped with heteroatoms at the interface between the negative electrode and LLZTO. After the molten metal lithium completely wets the ceramic sheet, it is cooled to obtain the Li|LLZTO@C integrated electrode. The above operations are all carried out in a glove box, with a water content of <0.01ppm.

[0084] In order to investigate the ability of heteroatom-doped hard carbon to inhibit lithium dendrites, a battery with the structure of "Li / mixed conductive interlayer / LLZTO / heteroatom-doped hard carbon" was assembled. Lithium was deposited on the heteroatom hard carbon side. When the capacity was increased from 0.1 mAh cm -2 Increased to 0.6 mAh cm -2 , SEM pictures are as follows Figure 3 As shown, from Figure 3 It can be seen that metallic lithium is deposited in the form of large spheres on the heteroatom-doped hard carbon skeleton with a diameter of about 5 μm. The grown lithium nuclei are uniform and smooth, and whisker-like or dendritic growth is avoided. -2 and 0.3 mAh cm -2 When the lithium nucleus is formed, the morphology of the entire substrate is composed of a single layer of large spherical lithium. The nucleated lithium is coated by hard carbon to form a Li@C structure. This carbon-coated structure makes the electric field around the lithium nucleus more uniform and promotes the isotropic growth of lithium. This shows that the introduction of the heteroatom-doped hard carbon skeleton can effectively inhibit the growth of lithium dendrites. These improvements are mainly due to the effective regulation of lithium nucleation and subsequent growth processes.

[0085] Assembly of all-solid-state metal symmetric battery: Similarly, the other side of LLZTO was treated in the same manner as the above steps (1), (2), and (3) to obtain a Li / LLZTO@C / Li symmetric battery, which was finally packaged for testing.

[0086] The current impedance diagram of the assembled symmetrical battery is shown in Figure 4 As shown, the EIS results indicate that the modified all-solid-state metal lithium symmetric battery has lower interfacial impedance.

[0087] The assembled all-solid-state lithium metal symmetric battery is 2 The long-term cycling performance at current density is shown in Figure 2. Figure 5 As shown in the figure, the modified all-solid-state lithium metal symmetric battery can be used at 1.0 mA cm -2It can be stably cycled for 2000 hours at a high current density, indicating that the modified interface has excellent stability and can effectively inhibit the growth of lithium dendrites. The voltage curve maintains a flat and smooth platform during the cycle, indicating that lithium ions have a fast kinetic transmission channel at the interface.

[0088] The critical current density of the assembled symmetric battery is shown in Figure 6 As shown, from Figure 6 It can be seen that the modified all-solid-state lithium metal symmetric battery has an ultra-high critical current density of 4.0 mA cm -2 No short circuit occurred even at a current density of 2.5 %.

[0089] The interface scanning electron microscope cross-section image of the assembled symmetric battery after long-term cycling is shown in Figure 2. Figure 7 As shown, from Figure 7 It can be seen that the metal Li / LLZTO solid electrolyte interface still maintains excellent close contact, indicating that it has quite good stability.

[0090] After disassembling the all-solid-state symmetrical battery after a long cycle, the mixed conductive intermediate layer on the surface of the LLZTO ceramic sheet was analyzed by XPS after removing the metallic lithium. The results are as follows Figure 8 As shown, the full spectrum shows strong C, O, and F signals and weak Cl, N, and S signals, which indicates that the interface of the mixed conductive intermediate layer after cycling has substances such as LiF, Li2CO3, Li3N, and LiCl, further indicating that the doped elements in the mixed conductive intermediate layer in the Li|LLZTO@C integrated electrode have achieved lithiation.

[0091] Assembly of Semi-solid Lithium Metal Batteries: Preparation of NCM811 positive electrode sheet: Weigh NCM811 (nickel cobalt manganese oxide) ternary positive electrode material, conductive carbon, and binder in a mass ratio of 8:1:1. First dry grind for a period of time to evenly mix the above materials, then add an appropriate amount of organic solvent NMP for wet grinding to obtain a uniform slurry, which is coated on an aluminum foil current collector, baked for a period of time, and then cut into pieces to obtain NCM811 positive electrode sheets.

[0092] The prepared NCM811 positive electrode sheet, Li|LLZTO@C integrated electrode, and liquid electrolyte (1MLiPF6inDMC:EC:EMC=1:1:1 Vol% with 1%VC) were assembled into a battery to obtain a semi-solid lithium metal battery.

[0093] The charge and discharge curve of the obtained semi-solid metal lithium battery at 0.1C is shown in the figure Fig. 9 As shown, from Fig. 9 It can be seen that solid-state lithium metal batteries exhibit excellent charge and discharge performance, further demonstrating their potential for commercial application.

[0094] Example 2 Assembly of quasi-solid-state lithium metal battery: Preparation of LiFePO4 positive electrode sheet: LiFePO4, conductive carbon and binder are weighed in a mass ratio of 8:1:1. Dry grind the above materials for a period of time to evenly mix them, then add an appropriate amount of organic solvent NMP for wet grinding to obtain a uniform slurry, which is coated on an aluminum foil current collector, baked for a period of time, and then cut into pieces to obtain a LiFePO4 positive electrode sheet.

[0095] The prepared LiFePO4 positive electrode sheet, the Li|LLZTO@C integrated electrode prepared in Example 1, and the polymer solid electrolyte PDOL (poly 1,3-dioxolane) were assembled into a battery to obtain a quasi-solid-state lithium metal battery.

[0096] The charge and discharge curve of the assembled quasi-solid-state metal lithium battery at 0.1C is shown in the figure below: Fig.10 As shown, from Fig.10 It can be seen that solid-state lithium metal batteries exhibit excellent charging and discharging performance.

[0097] Example 3 The difference between this embodiment and embodiment 1 is that step (2) is different, specifically: interface modification: the oxide solid electrolyte LLZTO ceramic sheet is placed on a heating table for low-temperature preheating, and then the protein cream is coated on the surface of the preheated ceramic sheet. The ceramic sheet coated with protein cream is sent into a tubular furnace and directly heated to 600-1000°C at 5°C / min for high-temperature pyrolysis and kept warm for two hours, thereby introducing a hard carbon skeleton (doped atoms are N, F, S, K, Na, Cl) with a thickness of 2-3 μm on the surface of the ceramic sheet, and obtaining an oxide solid electrolyte ceramic sheet LLZTO@C with a hard carbon skeleton introduced on the surface, whose XRD pattern is shown as follows: Figure 1 The remaining steps are the same to obtain an all-solid-state metal lithium symmetric battery.

[0098] By comparing the XRD patterns of the hard carbon skeletons obtained in Example 1 and Example 3, it is found that the peak intensity of the hard carbon (002) peak after pretreatment in Example 1 is reduced, and the position moves to a low diffraction angle, indicating that the hard carbon after pretreatment in Example 1 has a more disordered structure, which greatly improves the ion storage capacity and provides more lithium ion binding sites.

[0099] Comparative Example 1 The only difference between this comparative example and Example 1 is that phenolic resin and sucrose are selected as carbon source precursors; the phenolic resin and sucrose are mixed in anhydrous ethanol in a certain proportion to form a precursor solution in which the phenolic resin and sucrose molecules are cross-linked.

[0100] Symmetrical cells and all-solid-state lithium metal symmetric cells were assembled in the same manner as in Example 1.

[0101] The assembled symmetric cell is at 0.1 mA / cm 2 The long-term cycling performance at current density is shown in Figure 2. Fig.11 As shown, from Fig.11 It can be seen that the hard carbon framework without heteroatom doping has poor stability, resulting in obvious polarization of the all-solid-state metal lithium symmetric battery after 100 hours.

[0102] The critical current density of the assembled symmetric battery is shown in Figure 6 As shown, from Figure 6 It can be seen that compared with the symmetrical battery assembled in Example 1, the critical current density of the symmetrical battery assembled in this comparative example is low, which further shows that the hard carbon skeleton without heteroatom doping has poor stability. After analysis, this is because the doping elements of the mixed conductive layer formed in Example 1 have been lithiated, and the lithiated LiF, Li3N, etc. can reduce the Li + The energy barrier for diffusion at the interface is uniform Li + Flux, promoting Li + Uniform deposition at the interface.

[0103] The schematic diagram of the modification method of Example 1 and Comparative Example 1 is as follows Fig.12 As shown, for Example 1, as shown in e, f, g, and h, the prepared protein cream is applied with a cotton swab on the LLZTO ceramic sheet, the protein cream solidifies on the ceramic sheet, and then is sent into a tubular furnace for carbonization to obtain a ceramic sheet with a hard carbon layer attached to the surface, and finally the molten lithium and the hard carbon layer are combined and lithified; for Comparative Example 2, as shown in a, b, c, and d, the prepared mixed solution is transferred with a rubber-tipped dropper and applied to the LLZTO ceramic sheet, and a hard carbon layer is obtained on the surface after carbonization in a tubular furnace, and finally the molten lithium and the hard carbon layer are combined and lithified.

[0104] Comparative Example 2 The material preparation method of this comparative example is basically the same as that of Example 1, except that the thickness of the heteroatom-doped hard carbon skeleton introduced on the surface of the LLZTO ceramic sheet is about 10 μm.

[0105] The all-solid-state lithium metal symmetrical battery was assembled in the same manner as in Example 1.

[0106] The assembled symmetric cell is at 0.1 mA / cm 2 The long-term cycling performance at current density is shown in Figure 2. Fig.13 As shown, from Fig.13 It can be seen that the all-solid-state lithium metal symmetrical battery showed obvious polarization after 580 hours, and an "arc-shaped" voltage curve appeared in the early stage of the cycle. This is because the transmission of lithium ions at the interface is hindered, and an ion diffusion concentration gradient appears. This shows that the thicker hard carbon skeleton has become a blocking layer for lithium ion migration.

[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode, characterized in that: The invention comprises an inorganic solid electrolyte sheet, a mixed conductive intermediate layer and a metal lithium layer, wherein the mixed conductive intermediate layer is located on one surface of the inorganic solid electrolyte sheet, and the metal lithium layer is located on a surface of the mixed conductive intermediate layer away from the inorganic solid electrolyte sheet; the mixed conductive intermediate layer is a lithiated product of a hard carbon skeleton doped with heteroatoms; the heteroatoms doped with the hard carbon skeleton are one or more of N, F, S, Cl, Na, and K; the lithiated product of the hard carbon skeleton doped with heteroatoms comprises hard carbon and LiC x , and one or more substances among LiF, Li2S, Li3N, and LiCl.

2. The metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode according to claim 1, characterized in that: The inorganic solid electrolyte sheet is one or more of an oxide solid electrolyte, a halide solid electrolyte, and a sulfide solid electrolyte; Preferably, the inorganic solid electrolyte sheet is selected from one or more of garnet oxide solid electrolyte, sodium superion conductor solid electrolyte, lithium superion conductor solid electrolyte, and perovskite solid electrolyte; The garnet-type oxide solid electrolyte is one or more of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum zirconium niobium oxide (LLZNO), and lithium gallium lanthanum zirconium oxide (LGLZO); The sodium superion conductor type solid electrolyte is one or more of lithium aluminum titanium phosphate (LATP) and lithium aluminum germanium phosphate (LAGP); The lithium superion conductor type solid electrolyte is one or more of lithium germanium vanadium oxide (LGVO) and lithium germanium phosphorus sulfur (LGPS); The perovskite solid electrolyte is ABO3, wherein A is one or more of Ca, Sr, and La; and B is one or more of Al and Ti; Preferably, the thickness of the mixed conductive intermediate layer is 2-3 μm.

3. A method for preparing a metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode, characterized in that: include: Forming a doped hard carbon layer on one surface of the inorganic solid electrolyte sheet to obtain an inorganic solid electrolyte sheet having a doped hard carbon layer on the surface; the doping atoms of the doped hard carbon layer are one or more of N, F, S, K, Na, and Cl; Under vacuum conditions with a water content of less than 0.01ppm or in an inert gas atmosphere, the metal lithium sheet is first heated to a molten state, and then the side of the inorganic solid electrolyte sheet having the doped hard carbon layer is placed on the molten metal lithium, and the lithiation reaction is carried out by keeping the temperature at a certain temperature to obtain a metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode.

4. The method for preparing the metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode according to claim 3, characterized in that: The thickness of the doped hard carbon layer is 2-3 μm.

5. The method for preparing the metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode according to claim 3, characterized in that: The step of forming a doped hard carbon layer on the surface of the inorganic solid electrolyte sheet comprises: coating a carbon source precursor on the surface of the inorganic solid electrolyte sheet, and then pyrolyzing the carbon source precursor in an argon atmosphere or a nitrogen atmosphere.

6. The method for preparing the metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode according to claim 3, characterized in that: The carbon source precursor includes biomass, and optionally sugars and synthetic resins; The sugar is selected from at least one of starch, glucose and sucrose; The synthetic resin is selected from at least one of phenolic resin, epoxy resin and urea-formaldehyde resin; The biomass is selected from at least one of egg white, honey, coconut shell, walnut shell, straw, wood, tea shell, and bamboo powder; Preferably, the pyrolysis comprises: firstly performing a low temperature heat treatment at 400-500°C, and then performing a high temperature heat treatment at 600-1000°C; Preferably, the low-temperature heat treatment time is 2 to 4 hours; the high-temperature heat treatment time is 2 to 4 hours.

7. The method for preparing the metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode according to claim 3, characterized in that: The temperature of the heated lithium metal sheet is 200-350°C; Preferably, the insulation temperature is 300-400°C.

8. The method for preparing the metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode according to claim 3, characterized in that: The inorganic solid electrolyte sheet is one or more of an oxide solid electrolyte, a halide solid electrolyte, and a sulfide solid electrolyte; Preferably, the inorganic solid electrolyte sheet is selected from one or more of garnet oxide solid electrolyte, sodium superion conductor solid electrolyte, lithium superion conductor solid electrolyte, and perovskite solid electrolyte; The garnet-type oxide solid electrolyte is one or more of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum zirconium niobium oxide (LLZNO), and lithium gallium lanthanum zirconium oxide (LGLZO); The sodium superion conductor type solid electrolyte is one or more of lithium aluminum titanium phosphate (LATP) and lithium aluminum germanium phosphate (LAGP); The lithium superion conductor type solid electrolyte is one or more of lithium germanium vanadium oxide (LGVO) and lithium germanium phosphorus sulfur (LGPS); The perovskite solid electrolyte is ABO3, wherein A is one or more of Ca, Sr, and La; and B is one or more of Al and Ti.

9. The method for preparing the metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode according to claim 3, characterized in that: The mixed conductive intermediate layer is a lithiated product of a hard carbon skeleton doped with a heteroatom; the lithiated product of a hard carbon skeleton doped with a heteroatom includes LiC x , LiF, Li2S, Li3N, LiCl and hard carbon.

10. A battery, characterized in that The battery comprises a metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode as described in claim 1 or 2 or a metal lithium / mixed conductive intermediate layer / inorganic solid electrolyte integrated electrode prepared by the preparation method according to any one of claims 3 to 9, and the battery is a semi-solid-state battery, a quasi-solid-state battery or an all-solid-state battery.

Citation Information

Patent Citations

  • All-solid-state lithium-sulfur battery

    CN106876783A

  • Composite lithium negative electrode, preparation method thereof and battery

    CN117038878A

  • Lithium metal secondary battery

    CN117638409A

  • Alkaline photoelectrochemical cell, process for its production and process for the light-driven production of hydrogen and oxygen

    DE102015003003A1

  • Nonaqueous electrolyte battery

    JP2011086554A